2021
DOI: 10.1159/000515420
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Calcium Dobesilate on Induced AKI in Severely Burned Mice

Abstract: <b><i>Background:</i></b> Early acute kidney injury (AKI) predicts a high mortality rate in severely burned patients. However, the pathophysiology of early AKI induced by severe burn has not been well-defined. This study was designed to examine the protective effects of calcium dobesilate (CaD) against severe burn-induced early AKI in mice and explore the mechanism. <b><i>Methods:</i></b> The shaved backs of mice were immersed in 100°C water for 10 s to make seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…In our study, we frst demonstrated that KAE lowers the expression of proinfammatory cytokines and increases the expression of anti-infammatory cytokines in septic AKI mice, thereby reversing AKI kidney injury. Akhter N et al reported that calcium dobesilate could reverse AKI injury in severely burned mice by inhibiting NF-κB/AKT expression [31], which is consistent with our study. Park et al found that kaempferol was able to reduce LPS-induced infammatory mediators by downregulating NF-κB and AKT [32].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we frst demonstrated that KAE lowers the expression of proinfammatory cytokines and increases the expression of anti-infammatory cytokines in septic AKI mice, thereby reversing AKI kidney injury. Akhter N et al reported that calcium dobesilate could reverse AKI injury in severely burned mice by inhibiting NF-κB/AKT expression [31], which is consistent with our study. Park et al found that kaempferol was able to reduce LPS-induced infammatory mediators by downregulating NF-κB and AKT [32].…”
Section: Discussionsupporting
confidence: 92%